Electronic Consultation Systems: Impact on Pediatric Orthopaedic Care. Issue 9 (October 2020) - Chang, Youjin; Carsen, Sasha; Keely, Erin; Liddy, Clare; Kontio, Ken; Smit, Kevin
Abstract : Background: The demand for pediatric orthopaedic surgery consultation has grown rapidly, leading to longer wait times for elective consultation in some regions. Some specialties are addressing this increased demand through electronic consultation services. We wanted to examine the impact of pediatric orthopaedic e-consultations in Canada's Eastern Ontario region. Methods: We developed a cross-sectional study of all the cases directed to a pediatric orthopaedic surgery specialist using the Champlain Building Access to Specialists through eConsultation (BASE) eConsult service over a 2-year period and examined their impact on in-person referrals, time of e-consultation and primary care satisfaction as well as types of clinical questions that were asked. Results: Electronic consultations avoided in-person appointments in 68% of the submitted cases. The median response by specialists received by the primary care providers (PCPs) was <20 hours. A total of 69% of consultations involve >1 type of clinical questions, most commonly about basic trauma/fracture care and management recommendations. Ninety-seven percent of the PCPs found the overall value for the care of the patients to be good or excellent. Conclusions: This cross-sectional study demonstrates the effective and timely use of eConsult in pediatric orthopaedic surgery. It also shows a significant reduction in the number of in-person consultations required and demonstrates a high satisfaction rate by PCPs using the service. Clinical Relevance: In addition to the efficacy and time-sensitive care provided to the patients, the study shows that, professionally, 89% of PCPs found this service to be excellent or good. The broader implications of electronic consultation on overall quality of care, population health, and patient satisfaction requires further investigation.